Novela hispanoamericana de fin de siglo - MEYER-MINNEMANN, Klaus (FONDO DE CULTURA ECONOMICA, 1991)
Contenido:RODO, E.; SILVA, José A.; MARTI, José; CAMBACERES, E.; GARCIA MEROU; REYELES, C.; DOMINICI, P.; SOTO-HALL, M.; LARRETA, Enrique; ESTRADA, Angel de etc.